2019
DOI: 10.1039/c9cc02856k
|View full text |Cite
|
Sign up to set email alerts
|

A guanylurea-functionalized conjugated polymer enables RNA interference in ex vivo human airway epithelium

Abstract: Positive charge modulation chemistry via the guanylurea group allows an efficient target gene knockdown in primary normal human bronchial epithelial cells covered with mucus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, there was little information about the microglial population in the spinal cord and how these cells react following injury. The dynamic response of microglia cells to SCI has been confirmed in many studies [ 8 , [116] , [117] , [118] , [119] ]. Lacroix et al in a study have shown that microglia are immediately recruited in the injury site in the spinal cord.…”
Section: Astrocyte-derived Inhibitors Causing Demyelination and Reducmentioning
confidence: 75%
“…However, there was little information about the microglial population in the spinal cord and how these cells react following injury. The dynamic response of microglia cells to SCI has been confirmed in many studies [ 8 , [116] , [117] , [118] , [119] ]. Lacroix et al in a study have shown that microglia are immediately recruited in the injury site in the spinal cord.…”
Section: Astrocyte-derived Inhibitors Causing Demyelination and Reducmentioning
confidence: 75%
“…In everyday life, it is one of the most common polymers. In laboratory, however, polystyrene has also been widely used as a reference material to assess average molecular weights and weight distribution of polymers and macrocycles via gel permeation chromatography 30,31 . In this work, particles with an average diameter of 2.68 μm and PDI of 2.3% have been synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…After synthesizing a guanidine‐containing poly(oxanorbornene imide) (G, Figure 1), phenyl isocyanate was reacted with guanidine to synthesize the Ph‐CG containing PN. Synthesis of Bz, PhPr, and PhBu was done via the reaction of the respective primary amines and the N,N′‐di‐boc‐guanidine containing PN [36] . Random and block copolymers with repeating units bearing both guanidine and aromatic benzyl side chains (random‐Bz‐G and block‐Bz‐G) were also synthesized as control PNs (Scheme S1 and S2).…”
Section: Figurementioning
confidence: 99%
“…Synthesis of Bz, PhPr, and PhBu was done via the reaction of the respective primary amines and the N,N'-di-boc-guanidine containing PN. [36] Random and block copolymers with repeating units bearing both guanidine and aromatic benzyl side chains (random-Bz-G and block-Bz-G) were also synthesized as control PNs (Scheme S1 and S2).…”
mentioning
confidence: 99%